Revisiting Neutrophil-to-lymphocyte Ratio and De Ritis Ratio as Glycemic Control Assessment Tool among Type 2 Diabetes Mellitus: A Retrospective Study - Asharani Ningappa; Mahanth Nagaraju (Indian Journal of Medical Biochemistry)
Aims and background: Diabetes mellitus (DM) is a chronic hyperglycemic state with high morbidity and mortality. Chronic inflammation is pivotal in the pathogenesis and progression of micro and macrovascular complications in diabetes. Neutrophil-to-lymphocyte ratio (NLR) and De Ritis ratio are indicators of subclinical systemic inflammation. The study aimed to compare NLR and De Ritis ratios at different levels of glycemic control and find the best cut-off value for NLR and De Ritis ratio to assess glycemic control among type 2 DM (T2DM) patients. Materials and methods: It is a retrospective study done on diabetic patients. A total of 120 clinically diagnosed DM patients, were grouped based on HbA1c value as good glycemic control (HbA1c ≤ 7.5%) group (G-I, n = 52) and poor glycemic control (HbA1c > 7.5%) group (G-II, n = 68). Data was expressed as mean ± SD for continuous variables and frequency and percentage for categorical variables. Student's t-test was used to compare the two groups’ means. Receiver operator characteristic (ROC) curve analysis was performed to identify the optimal cut-off point of NLR and De Ritis ratio for the prediction of poor glycemic control. Statistical significance was set at p < 0.05. Results: Out of 120 subjects, 52.5% (n = 63) were in the age-group of 40–60 years and most of them (68.25%) had poor glycemic control with a mean HbA1c level of 10.0 ± 1.5 %. The mean total leukocyte count (TLC) count was not statistically significant among the two groups (G-I = 10.04 ± 3.5 and G-II = 10.04 ± 4.4, p = 0.99) but the NLR was higher in group II than in group I and was statistically significant (G-I = 2.7 ± 2.3 and G-II = 3.9 ± 2.6, p = 0.001). Even though the AST and alanine transaminase (ALT) values were not statistically different among the two groups, the De Ritis ratio was higher among group II and was statistically significant (G-I = 1.1 ± 0.3 and G-II = 1.3 ± 0.6, p = 0.02). The area under the curve (AUC) for NLR and De Ritis ratio was 0.637 and 0.539, respectively. The optical cut-off values for NLR and De Ritis ratio to categorize poor glycemic control were ≥2.01 and ≥1.03, respectively. Conclusion: The NLR and De Ritis ratio are elevated in patients with poor glycemic control, even if absolute levels of TLC, aspartate transaminase (AST), and ALT remain largely unchanged. In diabetic patients, the ROC analysis showed that NLR provided better discrimination for poor glycemic control compared to the De Ritis ratio. Therefore, NLR, particularly at a threshold value of ≥2.01, may be a reliable indicator of poor glycemic control and a preferable predictive marker over the De Ritis ratio.